Study on mechanism of concrete crack development control based on LDH and microbial carbon fixation mineralization - X. Li; Q.W. Zhan; C.H. Fu; X. Zhang; Y.Q. Zhao (Case Studies in Construction Materials)
The distribution area of the self-healing products of microbial remediation agents in cementitious materials was an indicator of the environmental adaptability and mineralization capacity of microorganisms in the cracked region. The morphology and quantity of mineralization products by microorganisms varied under different pH conditions, with particularly poor mineralization effects observed in highly alkaline environments. Therefore, a bimetallic hydroxide composite microbial system was employed to enhance the microenvironment of the pore solution. This study systematically analyzed the distribution pattern of the repair products in cementitious materials by investigating the microbial mineralization and hydration products of metal phase inorganic minerals. Firstly, the microstructure and mass distribution of microbial mineralization products were analyzed at different pH values to identify the optimal mineralization pH environment for microorganisms. Secondly, the hydration products of selected calcium-based inorganic minerals and aluminum-based inorganic minerals in simulated seawater pore solution were investigated, focusing on their capacity to fix Cl- and SO42- ions and regulate pH values. Additionally, SEM, EDS, XRD, FTIR, and DTA techniques were employed to analyze the composition and morphology of the products at different time intervals, confirming the formation of bimetallic hydroxides. Finally, the repair agent was applied for actual repair in cementitious materials, and the repair products at different depths of the cross-section were analyzed using SEM, EDS, XRD, FTIR, and DTA to verify the distribution of different types of repair products at varying depths. It was established that microbial components and metal phase inorganic mineral components exerted distinct effects in different regions, with microbial components mineralizing and sealing cracks, while inorganic mineral components hydrated to improve the microenvironment of the solution.